ASPEK PERFORMATIF DAN INFOMATIF HADIS DALAM FILM ANIMASI NUSSA EPISODE BUKAN MAHRAM - Najibur Rohman; Khotibul Umam, Rohman, Junaidi, Fatichatus Sa’diyah (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research is motivated by the rampant behaviour of ‘shaking hands’ which is increasingly being done by humans. Hand-shaking behaviour is a way of dressing people that is not as usual to look different with the aim of attracting the attention of others and acting arrogant. This handshaking behaviour is a behaviour that is disliked by the Prophet (SAW) and it is even mentioned that Allāh SWT threatens to dress the perpetrators of shaking hands in the world in clothes of humiliation in the hereafter. This research refers to identifying the object of reception in terms of informative and performative functions. Hadith Shuhrah in the film "Nyentri: A Short Film of the Hadith of Rasulullāh SAW’. Based on the research focus that has been formulated, this research specifically aims to find out or identify informative aspects and performative aspects as part of one of the methods of living hadith reception of Hadith Shuhrah in the film ‘Nyentri: A Short Film of the Hadith of Rasulullāh SAW’. To identify these problems, the research uses a descriptive qualitative method of case study type because it aims to describe the informative and performative aspects or forms of hadith reception in the film ‘ Nyentri: A Short Film of the Hadith of Rasulullāh SAW’. The findings or conclusions of this study are the existence of the hadith of Shuhrah recited by one of the characters in the film so that it is identified as a reception of the informative function aspect, after a search was made for the hadith, it was found that the hadith was narrated by Ibn Mājah and Abū Dawūd in their books. Furthermore, the response of the characters to Shuhrah ‘s hadith that had been recited in the film was identified as the reception of the performative function aspect